Design of beam forming network for time‐modulated linear array with artificial bees colony algorithm. (22nd October 2014) - Ruchi, Ruchi; Nandi, Arnab; Basu, Banani
Abstract A novel technique of beam shaping and beam steering at the central frequency using uniformly excited time‐modulated linear array is proposed. Unlike conventional time‐switched antenna array, the technique utilises a common complex time exponential signal with unit amplitude at the switching frequency, while each element is controlled by radio frequency switches with unique switching intervals that results on a relative amplitude weight and phase difference between the elements at the central frequency without phase shifters. Artificial bees colony based approach is applied to approximate the switching intervals that produce the desired pattern at the fundamental frequency and suppress the sideband radiation losses. The paper presents an analytical evaluation of the power radiated by the array at the central frequency and power wasted at the sidebands and thereby calculates the dynamic efficiency of the proposed array considering a mutual coupling effect. Representative examples are shown and simulated using commercial electromagnetic simulation software to justify the applicability of the derived expression. Copyright © 2014 John Wiley & Sons, Ltd.